Coke’s secret ingredient: The power of storytelling - Singapore Management University (Institutional Knowledge at Singapore Management University, 2013)
Coca-Cola was a product developed during the manufacturing era of the second industrial revolution. In its 120-year history, the world has changed. How does Coca-Cola compete and stay relevant in the 21st century with technology brands like Google and Facebook dominating people’s attention? According to Leonardo O’Grady, Director ASEAN Integrated Marketing & Communications, Coca-Cola Asia Pacific, the key to success is engaging the market with great story-telling.